STRATEGI KOMUNIKASI KELOMPOK DALAM MOTIVASI BELAJAR SISWA MADRASAH TSANAWIYAH (MTs) AL-WASHLIYAH KABUPATEN BATU BARA - Mhd Syarifuddin; Muhammad Alfikri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Objective from his research is for know How strategy communication group in learning motivation student Of MTS AL-Washliyah Batu Bara Regency. Method study Which used in study This is descriptive analytical Which served in information form as detailed maybe and Then analyze it in shape words written. Options include in category qualitative with location study Which conducted by Madrasah Tsanawiyah, Subdistrict Fifty Coast, Regency Coal, North Sumatra. Source material study obtained through study literature. Then Source information appear from results interview deep with informant ie student MTS, Headmaster MTS AL-Washliyah, Then a number of teacher from MTS AL-Washliyah. Results study This describe communication group with use learning strategies active through method solving problem with student expectations can Study regularly active with solve problem Of class while do research only teacher Which solve problem for create intelligence, knowledge, Personality, morality noble and prowess life independent. Design Communication Which made by a person teacher Of MTS AL-Washliyah This is A Communication face against used when them expect effect change communicator behavior Because is more persuasive and use communicator (mediated communication), more often used for communication information through more contact Lots means communication, but very weak in confidence. Communication Application group led by the teacher MTS AL-Washliyah, in matter This teacher use method inquiry group Where matter This happens in this method involves student start from planning until determination women lessons and study method through study